Targeted Therapies and Biomarkers in Small Cell Lung Cancer - Taniguchi, Hirokazu; Sen, Triparna; Rudin, Charles M. (Frontiers in Oncology, 2020)
Small cell lung cancer (SCLC) is an aggressive malignancy characterized by rapid growth, early metastasis, and acquired therapeutic resistance. A majority of patients with SCLC have extensive-stage (ES) disease, defined as the presence of metastatic disease outside the hemithorax at first diagnosis. SCLC has been considered “a graveyard for drug development,” with chemotherapy remaining the standard treatment for first- and second-line management until quite recently. In contrast to NSCLC, identifying therapeutic targets in SCLC has been challenging, partly because driver mutations are primarily loss of function, involving the tumor suppressor genes RB1 and TP53 or currently untargetable (e.g. amplification of MYC family members). Recent gene expression profiling of SCLC cells lines, patient samples and representative murine models, have led to a proposed delineation of four major subtypes for SCLC distinguished by differential expression of four key transcriptional regulators (ASCL1, NEUROD1, POU2F3 and YAP1). Our understanding of the biology of SCLC has indeed significantly improved recently due to the continued efforts of the dedicated investigators in this field, but the therapeutic options remain dismal. While recent results from immunotherapy trials are encouraging, most patients demonstrate either primary or rapid acquired resistance to current regimens, highlighting the clear need to improve the effectiveness and expand the scope of current therapeutic strategies. In this opinion article, we will discuss recent developments in the treatment of SCLC, focused on current understanding of the signaling pathways, the role of immunotherapy and targeted therapy, and emerging biomarkers of response to therapy in SCLC.